The Effect of Special Exercises Using Different Resistance (Sand/ Weights) on the Development of (17 - 19) year Old Soccer Players' Special Strength - Ahmed Abdulazeen Faraj; Firas Mutasher Abdulreda (College of Physical Education and Sport Sciences, 2021)
The importance of the research lies in special exercises using different resistance on youth soccer players U19 for developing some physical abilities as well as identifying which resistant is better sand or weights on the level of abilities development. The researcher used the experimental method on (20) players who were divided into two equal experimental groups; the first group (10) players trained on sand ground while the other (10) players trained on grass field using sand weights. Special training were designed for each group with special intensity, frequency and volume. The research lasted for (10) weeks with 3 training sessions per week and each session lasted for (40 - 45) minutes. The data was collected and treated using proper statistical operation SPSS to conclude that special exercises using sand and weight developed all types of special strength (explosive strength, strength - speed, strength endurance) in both groups. Finally the researcher recommended the necessity of coaches paying attention to using different resistance (sand/ weights) to improve physical abilities of players.